A Philosophical Memoir: Notes on Bhaskar, Realism and Cultural Theory. Issue 2 (14th March 2016) - Roberts, John
Abstract : In this philosophical memoir I trace out the part that Roy Bhaskar's philosophy of science played in the development of a non-reductive account of realism in art and cultural theory in the 1970s and 1980s in the UK, and the part his Dialectic (1993) played in the theorization of the concept of the philistine developed by myself and Dave Beech between 1996 and 1998. Our de-positivization of the concept as a symptomatic negation of the bourgeois 'aesthete' drew extensively on Bhaskar's notion of absence (in this instance of cultural skill and sensitivity) as a real absence. This in turn, allowed us to bring Bhaskar's realism and Theodor Adorno's Aesthetic Theory into alignment, where the philistine plays a similar, if undeveloped and untheorized role. Overall, the article marks a recognition of the continuing possibilities of Dialectic for a theory of negation in contemporary art and cultural theory.